Associations Between Female Sex, Sarcomere Variants, and Clinical Outcomes in Hypertrophic Cardiomyopathy. (February 2021) - Lakdawala, Neal K.; Olivotto, Iacopo; Day, Sharlene M.; Han, Larry; Ashley, Euan A.; Michels, Michelle; Ingles, Jodie; Semsarian, Christopher; Jacoby, Daniel; Jefferies, John L.; Colan, Steven D.; Pereira, Alexandre C.; et al.
Abstract : Background: The impact of sex on phenotypic expression in hypertrophic cardiomyopathy (HCM) has not been well characterized in genotyped cohorts. Methods: Retrospective cohort study from an international registry of patients receiving care at experienced HCM centers. Sex-based differences in baseline characteristics and clinical outcomes were assessed. Results: Of 5873 patients (3788 genotyped), 2226 (37.9%) were women. At baseline, women were older (49.0±19.9 versus 42.9±18.4 years, P <0.001) and more likely to have pathogenic/likely pathogenic sarcomeric variants (HCM patients with a sarcomere mutation; 51% versus 43%, P <0.001) despite equivalent utilization of genetic testing. Age at diagnosis varied by sex and genotype despite similar distribution of causal genes. Women were 3.6 to 7.1 years older at diagnosis ( P <0.02) except for patients with MYH7 variants where age at diagnosis was comparable for women and men (n=492; 34.8±19.2 versus 33.3±16.8 years, P =0.39). Over 7.7 median years of follow-up, New York Heart Association III-IV heart failure was more common in women (hazard ratio, 1.87 [CI, 1.48–2.36], P <0.001), after controlling for their higher burden of symptoms and outflow tract obstruction at baseline, reduced ejection fraction, HCM patients with a sarcomere mutation, age, and hypertension. All-cause mortality was increased in women (hazard ratio, 1.50 [CI, 1.13–1.99], P <0.01) but neither implantable cardioverter-defibrillator utilization nor ventricular arrhythmia varied by sex. Conclusions: In HCM, women are older at diagnosis, partly modified by genetic substrate. Regardless of genotype, women were at higher risk of mortality and developing severe heart failure symptoms. This points to a sex-effect on long-term myocardial performance in HCM, which should be investigated further. Abstract : Supplemental Digital Content is available in the text.